Laparoscopic subtotal cholecystectomy a boon to difficult gall bladder - Singh, Santosh Kumar; Shukla, Devendra; Singh, Pradeep Kumar; Katyayan, Ila (International Surgery Journal, 2020)
Background: Subtotal laparoscopic cholecystectomy has been in practice to treat difficult gall bladder for 100s of years. It keeps the benefit of being a minimally invasive and single-stage procedure. Thus, it remains a better option over conversion to open cholecystectomy as well as cholecystostomy which was a two-stage surgery practiced in earlier days. Methods: It was a prospective study focusing on indications, type and complications of subtotal laparoscopic cholecystectomy. It also compared the per-operative and post-operative outcomes of all cases of subtotal laparoscopic cholecystectomy (48) with cases of laparoscopic cholecystectomy that were converted to open procedure (30) performed over a period of 1 year. Patients were followed for 12 months post-surgery. Results: Acute cholecystitis is one of the most common indication of subtotal cholecystectomy. Also, it was associated with lesser mean operative time, postoperative hospital stays and postoperative complications when compared with conversion (to open) cholecystectomy. Conclusions: Subtotal cholecystectomy is a better option than open cholecystectomy in cases of difficult gall bladder.